Asthma and COVID-19: is asthma a risk factor for severe outcomes? - Johnston,SL (Allergy, 2020)
When I first read the manuscript that accompanies this editorial, upon its online publication on February 19th 2020(1), COVID-19 had already killed 2118 people in China, but only one person in Europe - an 80-year-old tourist from China, who died in France on the 15th February. I read the manuscript with grim fascination, as it was clear that SARS-CoV-2 had spread very rapidly in China which already had 74,576 cases and in South Korea which already had 58 cases, and that it was then invading Europe also, as France already had 12 cases, Germany 16, the UK 9, Italy 3, Spain 2 and other countries too.